Simulation of micro hydro power based on river configuration at river upstream - Nur Azirah, Abdul Rahim (2013)
Micro hydro power is a reliable form of energy. Pelton and Turgo turbine are examples of turbine that can be applied to install Micro Hydro Power. The purpose of this paper is to determine the performance and efficiency of Micro Hydro Power at Panching Waterfall, to simulate the flow of upstream river configuration and to determine the suitable turbine to be installed at high head river. Small scale hydro power can be develop in rural areas for clean electrification. The velocity and flow rate of the waterfall is determined and applied to the analysis to identify the suitable turbine to be used. To obtain the results, simulation using ANSYS CFX is done. The solver can determine the output velocity and torque of the flow through the respective cup, and then theoretical results are determined using calculations. The efficiency of Pelton is 0.965 while Turgo is 0.969. The value of torque is determined from the simulation resuts. The value is 9.25 N.m for Pelton and 7.41 N.m for Turgo. The results are then compared with theoretical results which the value for Pelton is 1.4 N.m and 1.316 for Turgo. From these results, the power output is calculated and the values are 1487.5 and 1483.5 for Pelton and Turgo respectively. These results clearly show that Pelton Turbine is suitable for high head Micro Hydro Power. On the other hand, simulation results also shows that Pelton has higher power output than Turgo where the values are 1476 watt and 1465.5 watt respectively.